Verifying Parameters of Ground Data Processing for the Thermal Control System of Small Spacecraft AIST Based on Telemetry Data Obtained by Samara University's GCS. (2017) - Tkachenko, S.I.; Salmin, V.V.; Tkachenko, I.S.; Kaurov, I.V.; Korovin, M.D.
Abstract: The paper presents the results of verification of ground testing of the AIST-type small spacecraft thermal control system (TCS) based on telemetry data received during their in-orbit testing and operation by the ground control station (GCS) of Samara University. The study into the efficiency and operability of the TCS was carried out on AIST series small spacecrafts AIST#1 (RS-43as), launched on April 19, 2013 from Baykonur Cosmodrome as a by-cargo of Bion-M #1 spacecraft, and an experimental sample of AIST #2 (RS-41at) small spacecraft launched by Soyuz-2.1 v with the Volga insertion module on December 28, 2013, from the Plesetsk Cosmodrome.